Early life factors and dental caries in 5-year-old children in China. (September 2017) - Sun, Xiangyu; Bernabé, Eduardo; Liu, Xuenan; Gallagher, Jennifer E.; Zheng, Shuguo
Abstract: Objectives: This study aimed to explore the association between early life factors and dental caries among 5-year-old Chinese children. Methods: Data from 9722 preschool children who participated in the third National Oral Health Survey of China were analysed. Information on early life (birth weight, breastfeeding and age when toothbrushing started), child (sex, ethnicity, birth order and dental behaviours) and family factors (parental education, household income, place of residence, number of children in the family, respondent's age and relation to the child) were obtained from parental questionnaires. Children were also clinically examined to assess dental caries experience using the decayed, missing and filled teeth (dmft) index. The association of early life factors with dmft was evaluated in negative binomial regression models. Results: We found that birth weight was not associated with dental caries experience; children who were exclusively and predominantly formula-fed had lower dmft values than those exclusively breastfed; and children who started brushing later in life had higher dmft values than those who were brushing within the first year. Only one in seven of all children received regular toothbrushing twice per day, and only 34.7% had commenced toothbrushing by the age of 3 years. Conclusions: This study shows certain early life factors play a role in dental caries among Chinese preschool children and provides important insights to shape public health initiatives on the importance of introducing early toothbrushing. Clinical significance: The early environment, especially the age when parents introduce toothbrushing to their children, can be an important factor to prevent childhood dental caries.